Selective location and migration of poly(methyl methacrylate)- grafted clay nanosheets with low grafting density in poly(methyl methacrylate)/poly(styrene-co-acrylonitrile) blends. (5th January 2019) - Liu, Ting; Zhang, Haimo; Zuo, Min; Zhang, Wenjing; Zhu, Weipu; Zheng, Qiang
Abstract: The location and migration of poly (methyl methacrylate)-grafted clay (clay- g -PMMA) nanosheets with low grafting density in a phase-separated polymer blend of poly (methyl methacrylate)/poly (styrene- co -acrylonitrile) (PMMA/SAN) was investigated. The grafting density and molecular weight for grafted PMMA chains on the surface of clay nanosheets was about 0.04 chains/nm 2 and 7.8 × 10 4, respectively, indicating that the grafted chains might exhibit the mushroom-like distribution. With phase separation of PMMA/SAN blend matrix, the well-dispersed clay- g -PMMA nanosheets in the blend matrix were first located in the SAN-rich phase and then gradually migrated to the interface between PMMA and SAN. The first abnormal location of modified clay in the blend matrix might be attributed to the favorable interaction between clay- g -PMMA and SAN induced by the miscibility of grafted PMMA/surrounding SAN chains and the unfavorable interaction between clay- g -PMMA and PMMA without any interpenetration of grafted and matrix chains. The enhanced miscibility between grafted PMMA and surrounding SAN just began to be destroyed after being annealed for a long time, resulting in the final migration of clay- g -PMMA to the interface of PMMA/SAN (thermodynamic equilibrium state). Graphical abstract: The selective location of clay- g -PMMA nanosheets with low grafting density in PMMA/SAN blend matrix can be controlled by the miscibility variation for the grafted PMMA chains/SAN matrix chains. Image 1